2019
DOI: 10.1021/acs.orglett.9b01231
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activation of Cis-Vicinal Diols by Boronic Acids: Site-Selective Acylation of Carbohydrates

Abstract: Site-selective acylation of unprotected carbohydrates by using stable, storable, and easily handled imidazole-containing organoboronic acid catalysts is described. This catalytic process with low catalyst loading enables the introduction of a wide variety of acyl functional groups into the equatorial position of cis-vicinal diols in unprotected hexapyranosides with excellent site selectivity. This is the first example that uses a Lewis base-containing boronic acid to enhance the nucleophilicity of hydroxy grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 64 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…[8][9][10] They are important building blocks in the fields of bioactive compounds (Figure 2) [14][15][16][17] and material sciences. [18,19] They have also found applications, as catalysts, [20][21][22] protecting group of diols, [23] molecular recognition sensors, [24] separation tools, [25] and cell-penetrating carriers for peptide delivery. [26,27]…”
Section: Reactivity and Importance Of Alkenylboronates And Arylboronatesmentioning
confidence: 99%
“…[8][9][10] They are important building blocks in the fields of bioactive compounds (Figure 2) [14][15][16][17] and material sciences. [18,19] They have also found applications, as catalysts, [20][21][22] protecting group of diols, [23] molecular recognition sensors, [24] separation tools, [25] and cell-penetrating carriers for peptide delivery. [26,27]…”
Section: Reactivity and Importance Of Alkenylboronates And Arylboronatesmentioning
confidence: 99%
“…With the required starting material in hand, we turned our attention to the screening of initially described ethanolamine ester of diphenylborinic acid catalyst (Taylor's catalyst) 48 along with a boronic acid catalyst recently developed by Shimada and coworkers. 49 Under classic conditions, both catalysts afforded conversion to the desired product (Scheme 2). Encouraged by this finding, we therefore optimized the reaction with the Shimada catalyst since it offered slightly higher catalytic activity in these initial experiments.…”
Section: Scheme 1: Preparation Of the Catalysis-precursor Bisallyl-op1118mentioning
confidence: 99%
“…In fact, there are reports in which site-selective acylation has been considered a powerful means for synthesizing partially acylated polyol natural products with focus on structure-activity relationships. [20][21][22][23][24][25] In this regard, we have recently reported that imidazole-containing boronic acid acts as a highly active catalyst for the site-selective acylation of carbohydrates 26) (Chart 1). Our catalytic reaction allows us to introduce a wide variety of acyl functional moieties in the equatorial position of cis-vicinal diol of carbohydrates in a highly selective manner.…”
Section: Introductionmentioning
confidence: 99%